Liberal Studies in Hong Kong 1992-2014: a critical history - Cheng, Wing Ming, Clement (2018)
This thesis investigates the history of two Liberal Studies curricula in Hong Kong: Advanced Supplementary Level Liberal Studies (ASL LS) and New Senior Secondary Liberal Studies (NSS LS), which were introduced under two successive academic structures. The former follows the English Britain academic structure, with five-year junior and senior secondary, two further secondary years for matriculation, and a three-year undergraduate higher education. The latter resembles the Chinese academic structure with three years’ junior secondary, three years’ senior secondary and four year of undergraduate higher education. ASL LS formed part of the matriculation education curriculum and lasted for two years under the old academic structure; NSS LS is a component of a three-year senior secondary education under the new academic structure. The shift of academic structures in Hong Kong took place between 2009 and 2012, during which transition period both academic structures existed in parallel.